Dosimetry of [18F]TRACK, the first PET tracer for imaging of TrkB/C receptors in humans - Alexander Thiel; Alexey Kostikov; Hailey Ahn; Youstina Daoud; Jean-Paul Soucy; Stephan Blinder; Carolin Jaworski; Carmen Wängler; Björn Wängler; Freimut Juengling; Shirin A. Enger; Ralf Schirrmacher (SpringerOpen, 2023)
Abstract Background Reduced expression or impaired signalling of tropomyosin receptor kinases (Trk receptors) are found in a vast spectrum of CNS disorders. [18F]TRACK is the first PET radioligand for TrkB/C with proven in vivo brain penetration and on-target specific signal. Here we report dosimetry data for [18F]TRACK in healthy humans. 6 healthy participants (age 22-61 y, 3 female) were scanned on a General Electric Discovery PET/CT 690 scanner. [18F]TRACK was synthesized with high molar activities (Am = 250 ± 75 GBq/µmol), and a dynamic series of 12 whole-body scans were acquired after injection of 129 to 147 MBq of the tracer. Images were reconstructed with standard corrections using the manufacturer's OSEM algorithm. Tracer concentration time-activity curves (TACs) were obtained using CT-derived volumes-of-interest. Organ-specific doses and the total effective dose were estimated using the Committee on Medical Internal Radiation Dose equation for adults and tabulated Source tissue values (S values). Results Average organ absorbed dose was highest for liver and gall bladder with 6.1E−2 (± 1.06E−2) mGy/MBq and 4.6 (± 1.18E−2) mGy/MBq, respectively. Total detriment weighted effective dose EDW was 1.63E−2 ± 1.68E−3 mSv/MBq. Organ-specific TACs indicated predominantly hepatic tracer elimination. Conclusion Total and organ-specific effective doses for [18F]TRACK are low and the dosimetry profile is similar to other 18F-labelled radio tracers currently used in clinical settings.